2019
DOI: 10.1590/0034-7167-2018-0334
|View full text |Cite
|
Sign up to set email alerts
|

Caring for the carer: quality of life and burden of female caregivers

Abstract: Objective: To assess the quality of life and the burden of female caregivers. Method: Descriptive, cross-sectional, quantitative study carried out with 224 informal caregivers from March to July 2016. Three instruments were used: a characterization form for the caregiver, the WHOQOL-Bref questionnaire and the Zarit Burden Interview. The following tests were used: Cronbach’s Alpha, Kolmogorov-Smirnov, Kruskal-Wallis, Spearman and Mann-Whitney. Results: The mean age of caregivers was 51.8 years with a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 21 publications
(47 reference statements)
2
24
0
20
Order By: Relevance
“…A similar result was observed in another study carried out with informal caregivers who are part of a family health program, pointing out that the greater the overload, the lower the caregiver's satisfaction with their own health and quality of life, that is, individuals more overloaded by the task have a worse perception of their quality of life 30 . Another research study that included 224 informal female caregivers demonstrated that overload was negatively correlated with quality of life 31 . In addition, a research study pointed out that high levels of anxiety, depression and overload negatively influence the quality of life scores of informal caregivers 32 .…”
Section: /13mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result was observed in another study carried out with informal caregivers who are part of a family health program, pointing out that the greater the overload, the lower the caregiver's satisfaction with their own health and quality of life, that is, individuals more overloaded by the task have a worse perception of their quality of life 30 . Another research study that included 224 informal female caregivers demonstrated that overload was negatively correlated with quality of life 31 . In addition, a research study pointed out that high levels of anxiety, depression and overload negatively influence the quality of life scores of informal caregivers 32 .…”
Section: /13mentioning
confidence: 99%
“…In general, the responsibility for the care of the child is assumed by the parents or family members who do not have scientific training to do so. Faced with this new reality, the caregiver is in front of a universe that goes beyond the care demands, being able to experience negative feelings and difficulties related to new responsibilities [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Quanto aos participantes, as amostras variaram entre 60 a 2.990 participantes, sete estudos abordaram apenas o cuidador, seis díades cuidador / pessoa adoecida e um estudo contou com cuidadores informais e não cuidadores. Os participantes eram cuidadores de pessoas com doenças crônicas como Parkinson (Grün, Pieri, Vaillant, & Diederich, 2016), Alzheimer ou outras demências (Vaingankar et al, 2015;Cova et al, 2018;Reed et al, 2017;Häikiö, Cloutier, & Rugkåsa, 2020), Esclerose Lateral Amiotrófica (Bayen et al, 2015;Galvin et al, 2016), Câncer (Ramos-Campos, Redolat, & Mesa-Gresa, 2020), transtornos mentais (Alzahrani, Fallata, Alabdulwahab, Alsafi, & Bashawri, 2017), sobreviventes de AVE (Gbiri, Olawale, & Isaac, 2015) e limitações físicas (Araújo et al, 2019).…”
Section: Resultsunclassified
“…Os itens avaliam tanto questões referentes a sobrecarga objetiva (não tem tempo para si mesmo porque está cuidando, sua vida social está prejudicada porque está cuidando, sente que não tem dinheiro suficiente para cuidar somando as outras despesas) como a sobrecarga subjetiva (sente-se irritado quando ele está por perto, sente receio pelo futuro, sente-se envergonhado com o comportamento dele) (Gbiri et al, 2015;Hoang, Green, & Bonner, 2019;Bayen et al, 2015;Mora-Castañeda et al, 2016;Ramos-Campos et al, 2020;Araújo et al, 2019;Reed et al, 2017;Galvin et al, 2016;Grün et al, 2016).…”
Section: Resultsunclassified
See 1 more Smart Citation